A review of garnet deposits in western and southern Iran. Issue 1 (2nd January 2022) - Nouri, Fatemeh; Stern, Robert J.; Azizi, Hossein
ABSTRACT: Garnets show wide ranges of chemical compositions and are key minerals for reconstructing the thermodynamic evolution of metamorphic terranes. The properties of garnets – including Mohs hardness ~7, lack of cleavage, vitreous luster and multiple colors – also makes them useful as semi-gemstones. Garnets are widespread accessory minerals in igneous and metamorphic rocks of western and southern Iran and are especially abundant in skarns and regional metamorphic rocks. 45 garnet deposits of western and southern Iran show six associations: (1) skarn (35 locations); (2) peraluminous granitoid and rhyolite (4 locations); (3) alkaline granite (1 location); (4) metamorphic rocks (3 locations); and (5) ophiolites (2 locations). Distinct garnet compositions are found in each association: mostly grossular-andradite in skarn, Ti-andradite in alkaline granite, almandine in peraluminous granite and volcanic rocks, almandine-grossular in metamorphic rocks and andradite- uvarovite associated with ophiolites. Western and southern Iran garnets are mostly related to skarns around Cenozoic granitoid intrusions. Ti-rich garnet formed at the expense of clinopyroxenites in alkaline igneous complexes due to alkaline metasomatism. These associations are useful for understanding garnet semi-gemstone deposits in western and southern Iran.